2 - The Cinema, a Place of Tension in Colonial Africa: Film Censorship in French West Africa - Odile Goerg, (Afrika Zamani, 2022)
Although cinema quickly became an important leisure activity in colonial Africa, its development and impact have not been studied in regard to French colonies. After analysing the context in which movies were watched, mainly in the most important cities, this paper moves on to study the government’s attitude to- wards this new and potentially subversive activity. Censorship regulations were passed from the mid-1930s on, and censorship boards were organised, respon- sible for allowing or forbidding the screening of movies. The study considers the motives for censorship and its actual implementa- tion, the reactions of the audience and official responses (including closures), sometimes decided on the spot. Foreign movies, be they Egyptian, Hindu or American, sometimes allowed movies-goers to express not only their enthusi- asm, but also their feelings towards colonial authorities. Movies theaters became then a site of tension, especially in late colonialism. Although this paper focusses primarily on French colonies, its comparative dimension makes it an important contribution to the study of cinema-going in Africa.